Pemberian Pembebasan Bersyarat bagi Narapidana Narkotika pada Lapas Kelas I Madiun - Mochamad Fardhil Prismawan; Mitro Subroto (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
There are provisions concerning criminal sanctions in the implementation of criminal law. where there is a purpose of imposing criminal sanctions for convicted offenders. The purpose of the imposition of criminal sanctions should not be solely to encourage the existence of a retaliation. In this case the Correctional institution is one of the executors of the purpose of the penal system in the improvement system As stated in the legislation, a number of law enforcement efforts to ensure that inmates are punished to be aware of their mistakes, in order to correct themselves and will not repeat crimes as well as then they are acceptable to be returned by the community, actively participate in the development and live a fair living as a good citizen and responsible criminal law, accordingly on law regulations act No. 12 Of 1995 about correctional regulations to regulate all rights of inmates. In the first letter k section 14 of the Act (Act No. 12 of 1995) it says "Prisoners are entitled to parole". Likewise the rights of well-behaved inmates of narcotics justice. Following the current development of narcotic crimes is a complex crime, because narcotic crimes do perpetrators can become victims at once. Best coaching for inmates returning/integrating into society and not being electrically isolated with iron rods.